2015
DOI: 10.1080/14786419.2015.1038810
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of Peristrophe bivalvis extracts: promising potential for anti-snake venoms against Naja kaouthia and Trimeresurus albolabris venoms

Abstract: This study evaluates the in vitro anti-snake venom potential of Peristrophe bivalvis (PB) extracts against Naja kaouthia (NK) and Trimeresurus albolabris (TA) venoms, including inhibition of cytotoxic effects and enzymatic activities, and the binding-precipitation of extracts and venom proteins analysis. In addition, the antioxidant, cytotoxic and in vivo acute oral toxic activities of PB extracts are also reported. The in vitro cytotoxic and enzymatic analysis reveals that the ethanol extracts of stems and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Renealmia alpinia extracts provided protection against lethal effects of B.asper venom and had no toxic effects in mice (26). The same way Peristrophe bivalvis extracts with antivenom potential to Naja kaouthia and Trimeresurus albolabris, did not show toxic signs in rats (27) The toxicity of the seed extract of various species of Swietenia were previously described, in a recent study of acute oral toxicity of the seed extract from Swietenia mahagoni in a murine model, lesions suggestive of organ toxicity at doses of 25, 200 2000, 5000 mg/kg were not observed (28). In another study which the acute oral toxicity of seed extract from Swietenia macrophylla in rats at doses of 2000 mg/kg was evaluated, the results showed that seeds did not produce significant differences in weight, food and water intake, biochemical and hematological parameters, or macroscopic and histopathological changes in the organs of the treated animals compared with controls (6).…”
Section: Discussionmentioning
confidence: 92%
“…Renealmia alpinia extracts provided protection against lethal effects of B.asper venom and had no toxic effects in mice (26). The same way Peristrophe bivalvis extracts with antivenom potential to Naja kaouthia and Trimeresurus albolabris, did not show toxic signs in rats (27) The toxicity of the seed extract of various species of Swietenia were previously described, in a recent study of acute oral toxicity of the seed extract from Swietenia mahagoni in a murine model, lesions suggestive of organ toxicity at doses of 25, 200 2000, 5000 mg/kg were not observed (28). In another study which the acute oral toxicity of seed extract from Swietenia macrophylla in rats at doses of 2000 mg/kg was evaluated, the results showed that seeds did not produce significant differences in weight, food and water intake, biochemical and hematological parameters, or macroscopic and histopathological changes in the organs of the treated animals compared with controls (6).…”
Section: Discussionmentioning
confidence: 92%
“…Apart from decorating role in foodstuffs, P. bivalvis has many biological and pharmaceutical activities including the treatment of blood diseases, anti-hypertension, anti-hyperlipidemia, fungistatic and antibacterial properties [5][6][7][8]. Phaopongthai et al [9] reported that P. bivalvis ethanolic extracts had the anti-snake venom activity against Naja kaouthia and Trimeresurus albolabris venoms. Another study highlighted the effectiveness of P. bivalvis ethanolic extracts on inhibition of bacteria consisting of Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…By spectral analysis, Thuy et al [9] isolated the major component of the color aqueous extract of red P. bivalvis leaves which was so-called peristrophine. In this study, the color extract components of P. bivalvis varieties were also identified as photosynthetic pigments and anthocyanins.…”
mentioning
confidence: 99%